Synthesis, physical properties and electroluminescence of functionalized pyrene derivative. (August 2019) - Liu, Xinqun; Tian, Feng; Han, Yanbing; Song, Tingting; Zhao, Xiaohui; Xiao, Jinchong
Abstract: Developing novel polycyclic aromatic hydrocarbons with high stability is of great importance, as well for opto-electronic applications as to provide novel materials for organic soft matter devices. Here the synthesis of a cyclized arene 13 and the corresponding acene-functionalized pyrene derivative 8 are described. Both molecules have been characterized by FT-IR, NMR spectroscopy, and mass spectroscopy. Their opto-electronic properties were determined from their absorption and emission spectra and electrochemistry and by theoretical calculations. Molecules 13 and 8 exhibit respectively a strong orange and cyan fluorescence in dichloromethane with high fluorescence quantum yields of 0.45 and 0.84 respectively, and present enhanced photo- and thermal stability compared to other large acenes. The organic light-emitting diodes using 13 and 8 as emitters were fabricated by via spin-coating way. After optimization they exhibited a maximum brightness of 2647 cd m −2 at 16.4 V with CIE coordinate of (0.61, 0.39) and 5620 cd m −2 at 7.2 V with CIE coordinate of (0.28, 0.64), respectively. Graphical abstract: Cyclopenta-embedded arene exhibited good thermal and photostability, which was chosen as emitter for orange electroluminescent devices. Image 1 Highlights: Cyclopenta-embedded arene derivative was synthesized. This molecule exhibited excellent thermal and photostability. The fabricated devices based on this compound showed orange electroluminescence.